(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the animation of a particle in a two-dimensional potential well. The program was created by the author in an object-oriented programming language, and while the program is running, one can visually observe the particle probability density graph by changing the quantum numbers of particles in the potential well and the size of the well.